Intestinal obstruction and necrosis as a complication of a ventriculoperitoneal shunt in a child undergoing surgery for ileus - Mert Sahinoglu; Derya Karaoglu Gundogdu; Tamer Sekmenli; Mustafa Koplay; Ender Koktekir; Hakan Karabagli (Medicine Science, 2021)
A 3, 5-years-old girl was being followed for prenatal intraventricular hemorrhage and hydrocephalus. A ventriculoperitoneal shunt had been placed to treat progressive hydrocephalus 1 year after cesarean delivery. The shunt was revised 2 years later due to shunt dysfunction. Six months later, wound revision was performed at our hospital due to the presence of discharge from the cranial tip wound. The patient wasplaced on antibiotic therapy. One week later she was admitted with intermittent vomiting. Physicalexamination revealed right lower quadrant tenderness. Standing abdominal x-ray and abdominal ultrasound showed free fluid in the abdomen and intestinal wall thickening. Preliminary diagnosis was ileus and the patient underwent emergency surgery by a pediatric surgeon. During surgery, the catheter was observed to revolve around the jejunal segment like a cuff, disrupting intestinal nutrition and causing necrosis. The necrotic intestine was resected and end-to-end anastomosis was performed. Recovery was uneventful and she began oral feeding 5 days postoperatively. Abdominal complications of a ventriculoperitoneal shunt should be considered in the differential diagnosis in a child with a VPS who presents to the hospital with abdominal pathology. [Med-Science 2021; 10(2.000): 619-22]